2018
DOI: 10.1155/2018/3074819
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of Surgical Suction Tip Geometry for Flow Optimisation: Influence on Suction-Induced Noise Pollution

Abstract: Introduction Suction devices for clearing the surgical field are among the most commonly used tools of every surgeon because a better view of the surgical field is essential. Forced suction may produce disturbingly loud noise, which acts as a nonnegligible stressor. Especially, in emergency situations with heavy bleeding, this loud noise has been described as an impeding factor in the medical decision-making process. In addition, there are reports of inner ear damage in patients due to suction noises during op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 50 publications
3
9
0
1
Order By: Relevance
“…Regarding dentists and dental assistants, it was found that the aspirator, not the rotating instruments, was the most intense source of noise in the office [ 21 ]. The noise of the surgical suction can be reduced through innovative modifications and designs [ 92 ]. Another suggestion is that suctions should be used as little as possible and turned off completely when not required [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding dentists and dental assistants, it was found that the aspirator, not the rotating instruments, was the most intense source of noise in the office [ 21 ]. The noise of the surgical suction can be reduced through innovative modifications and designs [ 92 ]. Another suggestion is that suctions should be used as little as possible and turned off completely when not required [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decreasing noise pollution levels caused by surgical instruments and alarms, which are the main noise sources in the OR, 4 can be achieved through innovative equipment design. 61 As intraoperative music has significant beneficial effects, 12 implementing music through headphones for patients during surgery would both reduce unwanted noise pollution as well as provide music. Moreover, several studies have explored the use of intraoperative microphones and headphones for the OR team as well, 24,62 especially in regard to robotic surgery during which the surgeon is often placed at a considerable distance away from the operation table.…”
Section: Discussionmentioning
confidence: 99%
“…During each experiment, a 30‐s noise measurement was made for each tested device, with the noise level recorded over a wide range of frequencies between 20 and 20,000 Hz. Between 2 and 8 kHz, sounds are perceived as 10–20 dB louder than outside this range at the same intensity 35 and in this frequency range, we also find essential parts of speech information 36 . For the analysis, we are reporting the total sound level (TSL) as computed by the application.…”
Section: Methodsmentioning
confidence: 99%